How social performance indicators and leadership contribute to the development of non-profits - an approach to long-term care homes. (9th December 2021) - Alves, Ana; Carvalho, Amélia; Ferreira, Marisa R.
Presently, non-profit organisations (NPOs) are increasingly representative in society and largely contribute to the economic and social development of countries. This development is linked to the creation of social value through their proximity to citizens, flexibility, and sensitive format, since most NPOs are service providers. Our paper focuses on long-term care (LTC) homes, a very particular type of NPO, and aims to understand how social performance indicators and leadership contribute to the development of such organisations. For that purpose, we will identify the most important social performance indicators and the main leadership characteristics. Our results provide a better understanding of the non-profit sector, and we intend to raise awareness to the importance of NPO boards' characteristics and leadership traits, emphasising the need for a more professionalised NPO management style.